Analisis Tantangan Dan Peluang UMKM Di Indonesia Dalam Menembus Pasar Global Pontianak - Dewi Swangsa; Marcelina Putri Widayanto; Febriani Dovi; Mohamad Zein Saleh (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
The global market currently faces instability due to geopolitical pressures, supply chain disruptions, inflation, and changes in international trade policies. These conditions require MSMEs, including those in Pontianak City, to increase their competitiveness through digital adaptation, strengthening human resource capacity, and meeting international quality standards. Pontianak's MSMEs have shown significant growth, but still face challenges such as low digital literacy, limited professional financial record-keeping, a lack of understanding of export certification, limited capital, and inter-island logistics barriers. Previous studies have confirmed that digitalization, financial literacy, online marketing, and the use of fintech contribute positively to MSME performance. However, research gaps remain regarding export readiness, the digital transformation process towards global markets, and there is a lack of studies highlighting logistical barriers in regions outside Java, such as Pontianak. Various solutions, including digital mentoring, ongoing training, facilitation of halal and international certification, regulatory simplification, and microfinance support, have been shown to improve MSME readiness to enter international markets. This study uses a descriptive qualitative approach to explore the challenges, opportunities, and needs of Pontianak's MSMEs in penetrating the global market through interviews, field observations, and official documentation. The research results indicate that export opportunities for Pontianak's MSMEs are significant, but require a comprehensive and collaborative strategy. This study aims to provide an in-depth understanding of the dynamics facing Pontianak's MSMEs and to formulate strategic recommendations to help them increase their competitiveness and sustainability in the international market